2014
DOI: 10.1215/03616878-2395217
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Choice in Health Insurance Exchanges: Can We Make It Work?

Abstract: Under the Patient Protection and Affordable Care Act (ACA), consumer choice plays a critical role: it drives the competitive market in health insurance plans that will operate through health insurance exchanges. As the 2014 deadline for establishing exchanges approaches, states face choices: they can either allow the federal government to manage an exchange on their behalf; take on a minimalist role by managing a state exchange or partnering with the federal exchange; or assume an activist role--by aiming to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In the United States, as the reconstruction of financial markets continues to transform the way that financial services and products are provided, financial decisions have become more complex. Meanwhile, American families are more than ever making financial decisions regarding retirement preparation and health‐care plans as responsibilities have increasingly been shifted to individuals from governments (Lusardi and Mitchell, ; Nadash and Day, ). Within this increasingly complex decision environment, the degree to which individuals have sufficient financial knowledge has become crucial in determining their current and long‐term financial well‐being.…”
mentioning
confidence: 99%
“…In the United States, as the reconstruction of financial markets continues to transform the way that financial services and products are provided, financial decisions have become more complex. Meanwhile, American families are more than ever making financial decisions regarding retirement preparation and health‐care plans as responsibilities have increasingly been shifted to individuals from governments (Lusardi and Mitchell, ; Nadash and Day, ). Within this increasingly complex decision environment, the degree to which individuals have sufficient financial knowledge has become crucial in determining their current and long‐term financial well‐being.…”
mentioning
confidence: 99%
“…[19][20][21] Low literacy and numeracy impede choice. 22,23 Simulated exercises of insurance exchange choices show that people's efforts to choose a cost-effective plan are no better than chance. 24 Moreover, simulations illustrate that although the actuarial value of a plan provides some information about its value, out-of-pocket spending can vary between plans of equal actuarial value.…”
mentioning
confidence: 99%
“…In terms of search costs, evidence suggests that consumer decision-making deteriorates when confronted with too much choice [46,57,9,13,20]. Notably, Frank and Lamiraud [19] found that as the choice set offered to consumers in the Swiss health insurance system increased, their willingness to switch declined.…”
Section: Literature Reviewmentioning
confidence: 99%